Forever skills : the 12 skills to future proof yourself, your team and your kids - Flanagan, Kieran (Behavioural researcher and strategist); Gregory, Dan (Daniel) (John Wiley & Sons Australia, 2019)
What skills will matter most for work, business and life in the future? Where should you focus your energy and effort when the world is changing at an extraordinary rate? How can you future proof yourself, your organisation and your kids? In this ground-breaking book Kieran Flanagan and Dan Gregory have interviewed hundreds of successful business people, educators, futurists, economists and historians to uncover the key skills that will always be critical to success in business and in life. Where most futurists increase your sense of panic and anxiety with dystopian images of the not-too-distant future characterised by Artificial Intelligence (AI) taking our jobs, algorithms hacking our most private moments and Austrian-accented cyborgs raising our children, Kieran and Dan remind us that we need to look beyond the things changing around us and focus on the things that won't change within us. Identify the skills you have that will always be relevant Gain insight from business leaders, entrepreneurs, educators, sport leaders and more Learn why each skill matters, and how to make it stronger Discover the things that won ' t change as we inch toward the future These 12 FOREVER SKILLS are designed to set you up for whatever the future may throw at you plus help you get more success in your work and life, today.